2022
DOI: 10.5114/aoms/146204
|View full text |Cite
|
Sign up to set email alerts
|

Presence of cell-free fetal circRNA in maternal plasma

Abstract: IntroductionThere is an urgent need to find novel stable cell-free fetal (cff)-RNA in the maternal circulation to facilitate the advance of non-invasive prenatal testing (NIPT) to more effectively avoid birth defects.Material and methodsCircRNA microarray was used to detect the cff-circRNA in plasma.ResultsThere were cff-circRNAs from the fetus in the peripheral blood of pregnant women and persisted even until at least 24 hours after delivery. In addition, we found that cff-circRNA might have a specific expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…To further improve the accuracy of NIPT in prenatal aneuploidy screening, many scholars have explored various aspects of bioinformatics technology and software engineering to improve the technology [ 41 , 42 ]. Domestic scholars have found that cffRNA is more stable in maternal circulation [ 43 ]. Although NIPT has many clear advantages, the introduction of NIPT into routine antenatal care in many countries has also raised a number of ethical issues [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further improve the accuracy of NIPT in prenatal aneuploidy screening, many scholars have explored various aspects of bioinformatics technology and software engineering to improve the technology [ 41 , 42 ]. Domestic scholars have found that cffRNA is more stable in maternal circulation [ 43 ]. Although NIPT has many clear advantages, the introduction of NIPT into routine antenatal care in many countries has also raised a number of ethical issues [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finnish scholars systematically evaluated the commonly used computer algorithms from the perspective of software engineering, and summarized the shortcomings of each algorithm in order to better apply clinical work [33]. Chinese scholars have found that a more stable cffRNA in the maternal circulation [34]. Although NIPT has many obvious advantages in most cases, the introduction of NIPT into routine antenatal care in many countries has also caused some ethical problems [35].…”
Section: Discussionmentioning
confidence: 99%
“…The total RNA of plasma was extracted using TRIzol Reagent (Invitrogen, Gaithersburg, MD, USA) for microarray analysis as previously described [ 34 ]. Briefly, RNA was digested with RNase R, amplificated, labeled, purified, and quantified according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%